O sonho de modernização deságua no Rio Araguaia: apropriação e consolidação do rio como lugar de turismo: The dream of modernization drain on the Araguaia River: appropriation and consolidation of the river as a place of tourism (Revista de História da UEG (REVHIST), 2020)
Abstract: This article aims to analyze the appropriation of the Araguaia riverbanks because of the reflexes of the modernization process that took place in Goiás. From 1930, the Brazilian culture was valued through symbols that had been gestated since the nineteenth century, and this period of Brazil has particularities and great efforts to define a consciousness of national unity, capable of creating links with the idea of ​​people, nation and territory. It is in this context that we seek to incorporate the values ​​of the coast into the “sertão”. In subsequent decades, new government politics will favor the planned occupation of the central region of the country, affecting the appropriation of the banks of the Araguaia River.Keywords: Araguaia River. Modernization. Government politics.